Nilai Religi Najib Mahfudz Dalam Novel Aulad Haratina Qissah Rifa'ah (Kajian Sosiologi Sastra Karya Wellek dan Warren) - Afifah Laili Sofi Alif (Jurusan Bahasa dan Sastra Arab Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2020)
The novel Aulad Haratina is a philosophical symbolic novel hich is a new writing style for Najib Mahfudz after previously being a historical romantic and social realist. Tells the story about a group of people who are oppressed by the arbitrary behavior of the dukuh leaders by presenting he reformer figure Rifaah who has the similaritys story with Prophet Isa. The implied meaning is not clearly explained behind the creation of literary works, where this novel is a form of criticism by the author of Nasirs reign in Egypt. Apart from this, this novel especially the story of Rifaah has other implied meanings that contain religious values as an explanation of the sociological approach of Wellek and Warrens literary works. The purpose of this study was to determine the religious values which consisting of three dimensions. The dimension of Aqidah namely remembering Allah Taala that death must occur for every human being sure that rewards will befall the perpetrators of injustice. Afterwards the dimension of Shariah namely giving thanks for Allahs blessings, pray to god Allah, advice to keep oral, call on amar maruf nahi munkar. The dimension of Morality consist of despicable morality namely oppressive attitudes and extorting of villagers property, and praiseworthy morality is respecting parents, obedience of wives to husbands, changing evil with tenderness without violence, and others.